Strategi Peningkatan Ketahanan Pangan Rumah Tangga di Kota Pekanbaru - Afriyanni, Afriyanni; Gevisioner, Gevisioner; Rifai, Ahmad; Hayati, Kemala; Agusyani, Agusyani; Purwati, Purwati; Restu Kusumaningrum, Nugraheni (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
Efforts to realize household food security in Pekanbaru City are still not optimal, because there are still food insecure households. This study aims to identify and evaluate internal and external factors and formulate strategies to improve household food security in Pekanbaru City. This research uses qualitative research methods with data collection techniques: interviews, Focus Group Discussion (FGD) and documentation studies. The data analysis techniques used are evaluation of internal and external factors and SWOT analysis. The results of this study identified 26 strategic factors to improve household food security consisting of 12 internal factors and 14 external factors. The most important internal factor is the availability of food is quite good while the most important external factor is a strategic geographical location. Based on the results of the evaluation of internal and external factors, the strategy to improve household food security is in quadrant III with strategies to overcome weaknesses by taking advantage of opportunities. This study recommends five alternative W-O strategies which are then elaborated into several action plans to improve household food security in Pekanbaru City.